2014
DOI: 10.3389/fpls.2014.00272
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of thylakoid galactolipid biosynthesis coordinated with chlorophyll biosynthesis during the development of chloroplasts in Arabidopsis

Abstract: Biogenesis of thylakoid membranes in chloroplasts requires the coordinated synthesis of chlorophyll and photosynthetic proteins with the galactolipids monogalactosyldiacylglycerol (MGDG) and digalactosyldiacylglycerol (DGDG), which constitute the bulk of the thylakoid lipid matrix. MGD1 and DGD1 are the key enzymes of MGDG and DGDG synthesis, respectively. We investigated the expression profiles of MGD1 and DGD1 in Arabidopsis to identify the transcriptional regulation that coordinates galactolipid synthesis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 57 publications
(128 reference statements)
3
55
0
Order By: Relevance
“…Chlorophyll (Chl) is the most important pigment in plants and is usually embedded in the thylakoid membranes of chloroplasts [1,2]. Chl is a green pigment, essential for photosynthesis, that absorbs energy from sunlight in antenna systems and transfers the energy to the reaction centre [3].…”
Section: Introductionmentioning
confidence: 99%
“…Chlorophyll (Chl) is the most important pigment in plants and is usually embedded in the thylakoid membranes of chloroplasts [1,2]. Chl is a green pigment, essential for photosynthesis, that absorbs energy from sunlight in antenna systems and transfers the energy to the reaction centre [3].…”
Section: Introductionmentioning
confidence: 99%
“…Given the drastic decrease in PSI content in the PG-depleted cells, Chl biosynthesis must be directly or indirectly affected after the PG concentration in membranes drops below a critical value. Although it was recently suggested that galactolipid and Chl biosyntheses are coregulated during chloroplast biogenesis (Kobayashi et al, 2014), a response of the Chl biosynthetic pathway to the altered lipid content has not been examined.…”
mentioning
confidence: 99%
“…This kind of crosstalk in the initial phase of thylakoid membrane biogenesis would guarantee that lipid and protein syntheses are harmonized from the beginning to avoid unbalanced accumulation of the major classes of thylakoid constituents during chloroplast biogenesis [25]. In line with this, transcriptomic studies in Arabidopsis thaliana have recently revealed tight coordination between the expression of nuclear genes involved in later steps of both lipid and chlorophyll syntheses and genes coding for photosynthetic proteins [26]. Whether similar regulatory principles also operate in cyanobacteria is currently unknown.…”
Section: Synthesis Of Lipidsmentioning
confidence: 92%